2021
DOI: 10.1073/pnas.2020459118
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional mass cytometry analysis of NK cell alterations in AML identifies a subgroup with adverse clinical outcome

Abstract: Natural killer (NK) cells are major antileukemic immune effectors. Leukemic blasts have a negative impact on NK cell function and promote the emergence of phenotypically and functionally impaired NK cells. In the current work, we highlight an accumulation of CD56−CD16+ unconventional NK cells in acute myeloid leukemia (AML), an aberrant subset initially described as being elevated in patients chronically infected with HIV-1. Deep phenotyping of NK cells was performed using peripheral blood from patients with n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 51 publications
(79 reference statements)
3
31
0
Order By: Relevance
“…Contrary to HDs, in AML, we found a significantly altered distribution of NK cells with increased frequencies of PB- and BM-derived CD56 bright CD16 − and CD56 dim CD16 − NK cell populations. Overall, we observed a loss of CD56 expression on NK cells, which has also been observed by Chretien et al [ 10 ]. In addition, a reduction of cytotoxic NK cells was recently described in different hematological malignancies (including AML) and solid tumors, especially at the tumor sites [ 43 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to HDs, in AML, we found a significantly altered distribution of NK cells with increased frequencies of PB- and BM-derived CD56 bright CD16 − and CD56 dim CD16 − NK cell populations. Overall, we observed a loss of CD56 expression on NK cells, which has also been observed by Chretien et al [ 10 ]. In addition, a reduction of cytotoxic NK cells was recently described in different hematological malignancies (including AML) and solid tumors, especially at the tumor sites [ 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…The CD3 – CD56 dim CD16 − and CD3 – CD56 bright CD16 − NK cells have regulatory functions by secretion of different cytokines, such as interferon-gamma (IFN-y), upon exposure to the microenvironment [ 6 , 7 ]. The CD56 – CD16 + NK cells are defined as an unconventional NK cell subset increased in chronic infections and cancer and with significantly decreased effector functions [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells play a major role in the defense against AML cells. However, numerous studies, including ours, have reported defects in NK cells in AML patients which all severely impair the anti-tumor functions and affect the clinical outcomes (29)(30)(31)(32)(33)(34)(35). These defects include alteration of maturation, reduced cytotoxic functions, downregulation of triggering receptor expression or up-regulation of inhibitory/regulatory receptors, or down-regulation of transcription factors important for NK cell functions (29,30,36,37).…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, an accumulation of CD56 − CD16 + unconventional NK cells, which correlates with poor prognosis, is observed in AML. These NK cells had decreased NKG2A, NKp30, NKp46, NKG2D, DNAM-1 and CD96 [122]. Other contradictory results are observed.…”
Section: Variation Of Nk Cells In Aging and Cancermentioning
confidence: 90%